Свадебный марш на балалайке: [роман] / Маргарита Южина - Южина Маргарита Эдуардовна (Иронический детектив, 2004)
Экземпляры: ф.23 (2007) / Инвентарный номер: 51659 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ю 18 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44